Staff members’ satisfaction level with the ministry of health and social services strategic plan implementation at three intermediate public hospitals in Namibia - Abner Kukeyinge, Shopati; Mitonga, Kabwebwe Honore; Albert Johannes, Isaacs (International Journal of Health, 2017)
This research aims to explore the staff remembers satisfaction level with strategic decisions implementation in the three intermediate public hospitals in Namibia. Reviewing the literature, 27 variables were identified. The items were then reduced using exploratory factor analysis, which is evaluated using Principal Axis Factoring with Direct Oblimin rotation. Using exploratory factor analysis, variables were categorized into 5 implementation perspectives. This model, in the order of effect, identified Service Provision with a predictor importance of (0.79), Human Resources Management (0.07), Governance (0.06), Financial Management (0.05) while, the Infrastructure Development and Management with predictor importance of (0.03) is the least important. This implies that the Service Provision theme is perceived by the MoHSS staff as having the largest impact of implementation satisfaction and quality of service perceptions at the three intermediate public hospitals. The radar chart also shows that the respondents perceived levels of satisfaction with strategy implementation is rated less than desired levels (yellow) of implementation superiority. The only item perceived to perform better than minimum level (blue) is related infrastructures development and management (IDM-2), Improve health facilities to be responsive to emerging needs’’. This implies that the strategic plans implementation level failed to meet the minimum satisfaction level of the operational staff and hospitals management teams. This further implied that top management shall be recognized that operational staff and hospitals management teams can turn strategic plan implementation into success.